Novel Processing Technology of Dairy Products - Moschopoulou, Ekaterini (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The conversion of milk to different dairy products is a technological process that has been in use for hundreds of years. Most dairy products are produced at a commercial scale using traditional methods and therefore, many efforts have been made to introduce novel technologies in their manufacture for improving their quality in general. More specifically, modern processing approaches may be used with the aim to develop new dairy products, to extend their shelf life, to change their textural properties, to ensure their safety or to increase their nutritional and health value. High Hydrostatic Pressure treatment, Ultrasound Processing, Pulse Electric Field treatment and Membrane Processing are some of these novel processes, which may be used in milk, yoghurt and other dairy product processing. Moreover, new dairy ingredients can be produced after enrichment with milk components, while modern analytical methods, such as nuclear magnetic resonance (NMR) and X-ray microtomography, are used for testing the main properties of dairy products.